2011
DOI: 10.1016/j.neulet.2010.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the extraocular motor nuclei innervate monkey palisade endings

Abstract: Research highlights▶ Neuronal tracer was injected into the abducens nucleus of monkey. ▶ Tracer positive axons were observed in the lateral rectus muscles. ▶ Tracer positive axons were cholinergic and established motor terminals. ▶ Palisade endings in the lateral rectus contained tracer as well. ▶ This study shows that palisade endings originate from motor nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…[18][19][20] Combining anterograde tracer labeling and molecular analyses, we demonstrated that axons supplying palisade endings established several motor contacts alongside the muscle fibers in a manner equal to that of en grappe motor terminals on MIFs. 20 These findings strongly suggest that palisade endings arise from MIF motoneurons in the EOM motor nuclei although receptors for cholinergic transmission have not been found in palisade endings so far with the exception of rabbit and rat.…”
Section: Developmental Support For a Mif Motoneuronpalisade Ending Comentioning
confidence: 89%
“…[18][19][20] Combining anterograde tracer labeling and molecular analyses, we demonstrated that axons supplying palisade endings established several motor contacts alongside the muscle fibers in a manner equal to that of en grappe motor terminals on MIFs. 20 These findings strongly suggest that palisade endings arise from MIF motoneurons in the EOM motor nuclei although receptors for cholinergic transmission have not been found in palisade endings so far with the exception of rabbit and rat.…”
Section: Developmental Support For a Mif Motoneuronpalisade Ending Comentioning
confidence: 89%
“…Because we never saw tracer labeled V mes cells after distal injections of the EOM, 16 this nucleus was ruled out as a source of PEs. In addition, tracer injections into the medullary part of V mes did not result in anterogradely labeled PEs 17 …”
Section: Discussionmentioning
confidence: 83%
“…The PEs represent special nerve endings unique to eye muscles, which are exclusively associated with MIFs at the myotendinous junctions of the muscle. PEs are found in all animals being investigated so far, and recently their cell bodies were shown to be located in or around the motor nuclei of EOMs 16, 17 . It is still not clear what function the PEs have and whether they are motor 14 or sensory 25 organs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the function of palisade endings remains unclear, it has been suggested they have both sensory and motor functions 15,16 . Recent anterograde tracing studies have confirmed that at least some cell bodies of palisade endings lie in the ocular motor nuclei 17,18 . Thus the ocular motor nerves could be an alternative conduit by which afferent inputs from the orbit reach the brain 15 .…”
Section: Discussionmentioning
confidence: 99%